Elevated Corticosterone Levels and Changes in Amphibian Behavior Are Associated with Batrachochytrium dendrobatidis (Bd) Infection and Bd Lineage - Gabor, Caitlin R. (PLoS One, 2015)
Few studies have examined the role hormones play in mediating clinical changes associated with infection by the parasite Batrachochytrium dendrobatidis (Bd). Glucocorticoid (GC) hormones such as corticosteroids (CORT) regulate homeostasis and likely play a key role in response to infection in amphibians. We explore the relationship between CORT release rates and Bd infection in tadpoles of the common midwife toad, Alytes obstetricians, using a non-invasive water-borne hormone collection method across seven populations. We further examined whether tadpoles of A. muletensis infected with a hypervirulent lineage of Bd, BdGPL, had greater CORT release rates than those infected with a hypovirulent lineage, BdCAPE. Finally, we examined the relationship between righting reflex and CORT release rates in infected metamorphic toads of A. obstetricans. We found an interaction between elevation and Bd infection status confirming that altitude is associated with the overall severity of infection. In tandem, increasing elevation was associated with increasing CORT release rates. Tadpoles infected with the hypervirulent BdGPL had significantly higher CORT release rates than tadpoles infected with BdCAPE showing that more aggressive infections lead to increased CORT release rates. Infected metamorphs with higher CORT levels had an impaired righting reflex, our defined experimental endpoint. These results provide evidence that CORT is associated with an amphibian’s vulnerability to Bd infection, and that CORT is also affected by the aggressiveness of infection by Bd. Together these results indicate that CORT is a viable biomarker of amphibian stress.